Concurrent Mental Illness and Financial Barriers to Mental Health Care Among a Nationally Representative Sample of Orthopaedic Trauma Survivors. Issue 12 (December 2022) - Jella, Tarun K.; Cwalina, Thomas B.; Vallier, Heather A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To understand prevalence and factors associated with concurrent mental illness and financial barriers to mental health care after orthopaedic trauma. Design: This is a retrospective, cross-sectional study. Setting: Interview-based survey was conducted across representative sample of 30, 000 US households. Patients/Participants: The study included 2, 309 survey respondents reporting a fracture over the past 3 months, between 2004 and 2017. Intervention: Screening for financial barriers to mental health care. Main Outcome Measurements: Prevalence and factors associated with concurrent mental illness and financial barriers to mental health care based on sociodemographic and injury characteristics were the main outcome measurements. Results: Of the 2309 orthopaedic trauma survivors included in our analysis, 203 patients [7.8%, 95% confidence interval (CI): 6.4%–9.2%] were determined to experience severe mental illness, of whom 54 (25.3%, 95% CI: 18.0%–32.6%) and 86 (40.9%, 95% CI: 31.5%–50.2%) reported financial barriers to counseling and pharmacotherapy, respectively. Factors associated with concurrent severe mental illness and cost barriers to care were 45 to 64 years of age [adjusted odds ratios (AOR) 5.1, 95% CI: 1.7–15, P = 0.004], income below 200% of the Federal Poverty Threshold (AOR 2.5, 95% CI: 1.2–5.3, P = 0.012), and unemployment at the time of injury (AOR 3.9, 95% CI: 1.4–11, P = 0.009). Conclusions: Approximately one half of orthopaedic trauma survivors with severe mental illness face financial barriers to some form of mental health services. Younger, minority, and low socioeconomic status patients are most affected. These data suggest the presence of postdiagnosis disparities in mental health access that may be improved through direct provision and subsidization of integrated mental health support services for high-risk populations. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.